Nitric oxide synthase activity in tissues of the blowfly Chrysomya megacephala (Fabricius, 1794) - Faraldo, Ana Carolina (2007)
Although insects lack the adaptive immune response of the mammalians, they manifest effective innate immune responses, which include both cellular and humoral components. Cellular responses are mediated by hemocytes, and humoral responses include the activation of proteolytic cascades that initiate many events, including NO production. In mammals, nitric oxide synthases (NOSs) are also present in the endothelium, the brain, the adrenal glands, and the platelets. Studies on the distribution of NO-producing systems in invertebrates have revealed functional similarities between NOS in this group and vertebrates. We attempted to localize NOS activity in tissues of naïve (UIL), yeast-injected (YIL), and saline-injected (SIL) larvae of the blowfly Chrysomya megacephala, using the NADPH diaphorase technique. Our findings revealed similar levels of NOS activity in muscle, fat body, Malpighian tubule, gut, and brain, suggesting that NO synthesis may not be involved in the immune response of these larval systems. These results were compared to many studies that recorded the involvement of NO in various physiological functions of insects.